Molecular phylogenetics and systematics of five genera of Malaysianmurine rodents (Maxomys, Sundamys, Leopoldamys, Niviventer and Rattus) inferred from partial mitochondrial cytochrome coxidase subunit I (COI) gene - Md Tamrin, Nur Aida; Abdullah, M.T (2011)
We genetically analysed 50 specimens of Murinae from Peninsular Malaysia and Sarawak, assigned to 12 species. Phylogenetic analyses of partial mitochondrial cytochrome c oxidase subunit I (476 base pairs) using four methods, namely, neighbour-joining (NJ), maximum parsimony (MP), maximum likelihood (ML) and Bayesian method resulted in similar statistically supported clades with minimal change in branching order. The analyses discovered that there were intermediate form of Maxomys species within M. whiteheadi and M. ochraceiventer populations. They display same external morphology as M. whiteheadi but genetically closer to M. ochraceiventer. Craniodental measurements showed significant differences between the three populations. Rattus and Sundamys appeared not fully resolved while Leopoldamys and Niviventer were steadily clustered. The intraspecific geographic variation in some species agrees with previous studies on the vicariance scenario and diversification of flora and fauna in Malaysia and Borneo.